The spatio-temporal trend of climate and characterization of drought in Borana Zone, Ethiopia - Sewmehon Sisay Fanta; Mamuye Busier Yesuf; Mulatu Tesfahun Merkos; Tamene Adugna Demissie (Scientific Reports, 2025)
Abstract This research assessed the Borana Zone’s climate trends and drought characteristics from 1991 to 2050. Using Innovative Trend Analysis (ITA), we quantified the climate and drought changes. The standard Precipitation and Evaporation index (SPEI) and self calibrated Palmer’s Droguht Severity Index (scPDSI) were selected to compute the drought’s magnitude. Precipitation significantly decreased from 1991 to 2020, with a variation from 2021 to 2050. Drought indices generally showed a decreasing trend. The short-term drought index (SPEI3) in the Mid-Moist (MM) category experienced the greatest decline, with a slope of − 0.055/year during the reference period. Under RCP4.5 scenarios, the SPEI3 for the Extremely-Most (EM) class showed the steepest decline at − 1.827/year. For RCP8.5, MM categories displayed significant reductions, with annual slopes of − 0.073, 0.021, and − 0.14 for SPEI3, SPEI12, and scPDSI, respectively. The moisture intensity also showed a diminishing trend, with scPDSI projected to decrease by 40.47% and 20.77% under the two emission scenarios. During the reference period, Near Normal (NN) moisture frequency varied from 71.39% to 82.81%, but is expected to decrease by 12% and 8% under the two scenarios. The adverse impacts can be mitigated by building the capacity of drought-vulnerable community.